The Legend of the Death of Uroš the Weak in Hagiographic Literature and Epic Poetry - Stojković, Marijana; Kostić Tmušić, Aleksandra S. (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Based on the tale of the death od Tsar Uroš, a medieval historical figure, known as Uroš the Weak, the paper attempted to reconstruct the traditional tale transposed into two, basically different genres—the Hagiography of Tsar Uroš by Patriarch Pajsije Janjevac and the epic poems of the pre-Kosovo thematic cycle: The Death of Dušan, Uroš and the Mrnjavčević Family, and The Death of Tsar Uroš. We analyzed how Patriarch Pajsije dealt with the issue of martyrdom in The Hagiography of Tsar Uroš, and how, on the other hand, the epic poetry covered the same motif. We also investigated how a legend performs as an independent genre, but also how, as a subgenere, it fits into a more comprehensive category contributing to the strengthening of the cult of Tsar Uroš. Furthermore, we looked at how the legend of the death of the „unfortunate” tsar was incorporated into hagiographical literature and an epic poetry. By examining the similarities and differences in the folklore of these two genres, we aimed to show how oral literature was convenient and, at the same time, essential for preserving the memory of famous figures and important events.